A new method for assessing hydrologic alterations based on the discharge hydrograph. Issue 14 (26th October 2021) - Guo, Xiaoming; Xu, Lukai; Su, Lei; Guo, Yan; Deng, Yu
ABSTRACT: Ecosurplus (ES) and ecodeficit (ED) based on flow duration curves have been used to assess hydrological alterations in contemporary research, but there are associated limitations. In this study a new method based on the discharge hydrograph is presented. The 12 monthly ESs and 12 monthly EDs constitute a new suite of indicators. Two types of equations are presented to calculate the degree of change in the ESs and EDs. A framework is proposed for classifying the risk of monthly EDs into four levels. Results show that inconsistencies among the eco-flows on different time scales ceased to exist. The second equation type showed a stronger performance in measuring the changes of monthly eco-flows. The risk graph intuitively demonstrates the risk levels of each month over past decades. The 24 indicators did not have strong correlations. This study is useful for water resource management considering the variations resulting from reservoir regulations.